Water quality assessment based on diatoms communities in the Sarawak River Basin, Malaysia / Hartini Mahidin … [et.al.]. - Mahidin, Hartini; Tambi, Hanita; Md Sofwan, Nurzawani (2016)
Sarawak is a state in Malaysia with the largest water resources and reserves due to huge land area and high annual rainfall. The Sarawak River Basin is part of the river başin system where it's valuable water resources is available to sustain life of residents in Kuching City and its surrounding areas. It has two main tributaries that flow through a catchment area which has been experiencing rapid social and economic development, which contributes to changes in land use for the past two decades. Dominant types of land use in this catchment area include the agricultural sector (oil palm, rubber, rice, pepper, horticulture and aquaculture), mining (gold, and quarry), industries (Samajaya, Bintawa and Sejingkat), commercial area (Kuching, Satok Market, Padawan, Bau) (Lau, 2011), settlements (Kuching, Padawan, 7th miles town, 12th miles town) (Kuok et al., 2011) recreational (golf courses, parks, sports fields and stadium and reserved forest (national parks, forest reserves and conservation areas) (Lau, 2011). Kuching city is inclusive of Kuching North and Kuching South located at the downstream of Sarawak River while three major towns of Bau, Batu Kawa and Siniawan are located at upstream of Sarawak River